Kitengela transforming: Will pastoralists and wildlife survive? - Reto-o-Reto Project (Reto-o-Reto Project, 2007)
The semi-arid Kitengela plains south of Nairobi National Park (NNP) have been the longtime home of the Kaputiei Maasai community. Together with NNP these plains form the Athi-Kaputiei ecosystem. The plains host rich populations of wildlife and are vital to the health of NNP, since 70 to 80 percent of the Park’s animals roam outside it’s boundaries at any one time. But the rangeland that once seemed endless is now splintering. Close to the ever expanding Nairobi, the Kitengela plains are experiencing a population boom, rising land prices and speculation, commercial and subsistence farming, and unregulated urbanisation. Maasai who once tended large cattle herds on communal land now often have a few animals on individual plots, and are selling off their own land for the cash to survive. Wildlife populations have dropped by more than 70 percent over 25 years. If present trends continue, the future may find - the Maasai dispossessed, a mere remnant of wildlife remaining in Nairobi National Park, severe water scarcity, and large areas of degraded land. Urgent planning and action involving all stakeholders is the best hope for giving Kitengela’s human, livestock and wildlife residents a healthy future.